2018
DOI: 10.1093/tas/txy109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of l-methionine vs. dl-methionine on performance, plasma concentrations of free amino acids and other metabolites, and myogenesis gene expression in young growing pigs

Abstract: Methionine (Met), the second or third limiting amino acid (AA) in typical swine diets, plays important roles in promoting swine health and growth, especially, muscle growth. Whereas dl-Met products have been used in swine industry for many years, l-Met products have been developed recently. This research was conducted to study the effects of supplemental l-Met or dl-Met on nutrient metabolism, muscle gene expression, and growth performance of pigs. Twenty crossbred young barrows (initial body weight [BW] 21.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Therefore, L-Met has a greater advantage in broilers during heat stress. However, Yang et al (2019) indicated that there was not difference in the expression of myogenesis-related genes and muscle growth in pigs fed with L-Met and DL-Met.…”
Section: Pectoral Muscle Histologymentioning
confidence: 90%
“…Therefore, L-Met has a greater advantage in broilers during heat stress. However, Yang et al (2019) indicated that there was not difference in the expression of myogenesis-related genes and muscle growth in pigs fed with L-Met and DL-Met.…”
Section: Pectoral Muscle Histologymentioning
confidence: 90%
“…The myogenic gene expression was analyzed by following our previously reported protocols [24]. Briefly, the total RNA was extracted from approximately 50 mg of muscle sample per pig using TRIzol Reagent (Invitrogen Corporation, Carlsbad, CA, USA) following the manufacturer's instructions.…”
Section: Analysis Of Myogenic Gene Expressionmentioning
confidence: 99%
“…The semi-quantitative polymerase chain reaction (PCR) analysis was performed using the Rotor-Gene SYBR Green PCR Kit with the Rotor-Gene Q System (Qiagen), followed by melting curve analysis to verify the specificity and identity of the PCR products [24]. The thermal cycling parameters were 95 • C for 5 min, followed by 40 cycles of 95 • C for 5 s and 60 • C for 10 s. Primers for the selected myogenesis-related genes, as well the hypoxanthine phosphoribosyl transferase 1 (Hprft1; as the endogenous control) gene, were manufactured at Integrated DNA Technologies (Coralville, IA, USA) with the primer sequences being adopted from Yang et al [24]. The Hprft1 gene was used for normalization of the potential variations caused during the sample preparation [25].…”
Section: Analysis Of Myogenic Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate dietary amino acid (AA) supply is often evaluated for pigs and most research has studied the requirements of a single AA; mainly the most limiting essential AAs in pig diets (Kiefer et al, 2005). There is much information about lysine requirements for different genetic groups, categories and sex of pigs (Santos et al, 2011), but there are few studies about the sulphur containing AAs (SAA) methionine (Met) and cysteine (Cys), mainly for starting pigs, since Met is typically the second or third limiting indispensable AA in grain-based swine diets (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%